Sewing in the Net – Collective-Aesthetical Experiences of Vestimentary Self-Fabrication - Venohr, Dagmar (ZoneModa Journal, 2020)
For a few years now some DIY bloggers have reflected the aesthetical development of the own and of the other in their vestimentary activities, in their creative production processes and in their collective-structured events. They design, construct and sew most of their garments. Sew-blogging reveals a self-generating form of collective vestimentary self-fabrication. This is directly linked to the aesthetic-practical agency, the sewing of clothes for themselves, the aestheticizing and showing of oneself in these clothes as well as the detailed description and visualization of the manufacturing process of the garments. In these forms of aesthetic communitization, an exclusionary fashion dictum can no longer prevail against the polyphonic emphasis and positive reinforcement of diversity, solidarity, and creativity through inclusive body awareness in collective self-sewn clothing. By an iconotextual analysis of the “MeMadeMittwoch,” a weekly moderated linking session in which the bloggers present each other their clothes sewn by themselves, the article reveals wherein the empowering moment of the fashion-agency lies, what is meant by vestimentary self-fabrication and how the collective-aesthetic appears between and within different medialization formations of the vestimentary.